Results of using cardiopulmonary bypass for spinal cord protection during surgical repair of complex aortic coarctation* - Sandrio, Stany; Karck, Matthias; Gorenflo, Matthias; Loukanov, Tsvetomir (Cardiology in the young, 2014)
Background - The aim of this study was to evaluate the surgical treatment of complex aortic coarctation using partial cardiopulmonary bypass to increase the spinal cord protection. - - - Methods - A total of 15 patients (age range from 7 to 48 years) underwent coarctation repair through a left posterolateral thoracotomy with cardiopulmonary bypass. Cannulation was performed via the descending aorta and the main pulmonary artery. In all, six surgeries were performed under hypothermic circulatory arrest and nine repairs were performed under mild hypothermia. The clinical outcome regarding the development of restenosis, as well as major neurologic complication, was studied. - - - Results - There was no mortality. None of the patients developed paraplegia. Of the 15 patients, two developed a recurrent stenosis at the proximal anastomosis between the aortic arch and the aortic prothesis at a mean follow-up of 5.5 years. In the remaining 13 patients, echocardiography and magnetic resonance imaging showed no evidence of a significant gradient. - - - Conclusion - Complex aortic coarctation without hypoplasia of the proximal aortic arch and intra-cardiac anomalies can be repaired with low mortality and neurologic morbidity via a left thoracotomy using cardiopulmonary bypass. The use of cardiopulmonary bypass goes along with a low risk of spinal cord and lower body ischaemia and provides a sufficient amount of time for the anastomoses.
46th Annual Meeting of the Association for European Paediatric and Congenital Cardiology, 24 May 2012, Istanbul, Turkey; 41st Annual Meetingof the German Society for Thoracic and Cardiovascular Surgery, 13 February2012, Freiburg, Germany
First published online: 7 February 2013
Gesehen am 07.10.2020